Descripción del nido de Phyllotis andium (Cricetidae: Phyllotini), en un matorral seco interandino en Ecuador - Nivelo-Villavicencio, Carlos (2021)
In this work, we describe the structure of the nest of Phyllotis andium Thomas, 1912 in an inter-Andean dry scrub in the south of the Azuay province in Ecuador, and the use of an introduced grass in their manufacture. Observations on sociability and abundance of this species are also presented. These data provide new information on the intraspecific relationships of these rodents and their natural history.